Efek Penggunaan Base Isolator Terhadap Periode Natural Bangunan Gedung Bertingkat yang Tereksitasi oleh Gempa - Rahmi Oktavia Cahyani; Ansadilla Niar Sitanggang (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2021)
A strong earthquake is an earthquake that emits very strong energy with a strength of more than 5 on the Richter scale that causes buildings to vibrate for some time. The natural period of the building is the length of time the building vibrates when the earthquake occurs until the earthquake stops which results in the risk of damage and even collapse of the building. One of the buildings that experienced the collapse was due to having a small natural period of the building so that the building was unable to withstand the vibrations caused by the earthquake to the maximum. To minimize the risk of collapse in buildings during an earthquake, one of them is planning an earthquake-resistant building by using a base isolator in order to increase the period of the structure so that it is able to soak up vibrations and slow down the movement of buildings that are excited by the earthquake. The purpose of this study was to determine the natural period of the building and the effect of using a base isolator when an earthquake occurred. The method used in this study is to plan buildings without base isolators and buildings with base isolators and analyze using the SAP2000 v.14 auxiliary program. The results of this study showed that the natural period of the building with Base Isolator in 3D increased 1.59 times for the X direction and 1.63 times for the Y direction. And the effect was a decrease in the displacement of the structure for the period by 66%, 46%, and 41% based on the three earthquake records.